Application of Mudharabah Contract on Business Capital Financing Products at BMT ANFA' NU - Umi Arifah; Achmad Nur Alfianto; Yeny Fitriyani (Mutanaqishah: Journal of Islamic Banking, 2024)
This research explores the use of mudharabah contracts in capital financing products at BMT Anfa' NU, an Islamic microfinance institution. Using qualitative methods, especially grounded theory, this study reveals that BMT Anfa' NU complies with the profit sharing principle determined at the beginning of the contract and provides funding on a weekly or monthly basis. The business capital financing products offered are in accordance with Sharia guidelines, with procedures that include application submission, document collection and feasibility assessment. This research provides a comprehensive understanding of the implementation of mudharabah agreements in financing business capital at BMT Anfa' NU, as well as the steps needed to access business capital through this sharia financial institution. In addition, this research provides practical recommendations to BMT Anfa' NU to improve the quality of mudharabah contract implementation and can serve as a guide for other Islamic microfinance institutions.